2000
DOI: 10.1002/rem.3440100305
|View full text |Cite
|
Sign up to set email alerts
|

Treatment technology for remediation of wood preserving sites: Overview

Abstract: This is the first in a series of five articles describing the applicability, performance, and cost of technologies for the remediation of contaminated soil and water at wood preserving sites. Site‐specific treatability studies conducted under the supervision of the United States Environmental Protection Agency (US EPA), National Risk Management Research Laboratory (NRMRL), from 1995 through 1997 constitute much of the basis for the evaluations presented, although data from other treatability studies, literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…[31][32][33][34][35][36][37][38][39] According to Stinson et al [40], the use of a biodegradation process allowed the removal of more than 94% of PCP initially present at concentrations ranging from 130 to 680 mg.kg -1 . Bates et al [41] showed that more than 82% of PAHs were removed after 400 days of treatment using a bioremediation process. Immobilisation techniques seemed to be efficient to simultaneously remove organic and inorganic contaminants from soils [42].…”
Section: Treatment Of Soil Contaminated By As Cr Cu Pcp and Pcddf 21mentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34][35][36][37][38][39] According to Stinson et al [40], the use of a biodegradation process allowed the removal of more than 94% of PCP initially present at concentrations ranging from 130 to 680 mg.kg -1 . Bates et al [41] showed that more than 82% of PAHs were removed after 400 days of treatment using a bioremediation process. Immobilisation techniques seemed to be efficient to simultaneously remove organic and inorganic contaminants from soils [42].…”
Section: Treatment Of Soil Contaminated By As Cr Cu Pcp and Pcddf 21mentioning
confidence: 99%
“…According to Xiao et al [49], soil washing in an alkaline medium (pH > 12) seemed to be very effective for the solubilization of PCP, with removal yields reaching 90%. The use of dimethyl ether (soil/dimethyl ether = 1/1), at 48°C was effective for the solubilization of more than 95% of the PCDDF and PCP originally present in [41] showed that the use of nonionic surfactant enhances the performances of soil washing to remove PAHs, PCP and PCDDF from contaminated soils. Indeed, these authors highlighted that the addition of a surfactant allowed an improvement of contaminants removals from 69 to 78%.…”
Section: Treatment Of Soil Contaminated By As Cr Cu Pcp and Pcddf 21mentioning
confidence: 99%
“…Currently the greatest sources of contamination are wood treatment facilities, landfills, and hazardous waste sites. More than 700 wood preserving sites have been identified in the United States, and many of these are contaminated with PCP. , Furthermore, the CERCLA Public Access Database lists 152 sites other than wood preserving sites that are contaminated with PCP . PCP leaches from these sites contaminating the groundwater.…”
Section: Introductionmentioning
confidence: 99%